The Effectiveness and Influences of the Navigation Ice Booms on the St. Marys River - Perham,R (1984)
Ice problems developed in the Sault Ste. Marie, Michigan, portion of the St. Marys River because of winter navigation Passing ships and natural influences moved ice from Soo Harbor into Little Rapids Cut in sufficient quantities to jam, cause high water in the harbor, and prevent further ship passage. After physical model and engineering studies, two ice booms with a total span of 1375 ft (419 m) with a 250-ft (76-m) navigation opening between were installed at the head of Little Rapids Cut in 1975. A modest field study program on the booms was conducted for the ensuring four winters to determine ice and boom interaction and the effects of ship passages on the system. Forces on some anchors were recorded and supplemental data were taken by local personnel. Several reports have been written about the booms' early operations. This paper presents four-year summary of the main effects of the booms on ice and ship interaction and vice versa. Throughout the four winter seasons, the small quantities of ice lost over and between the booms were manageable. Ships usually passed through the boom without influencing the boom force levels, but at time they brought about large changes. One boom needed strengthening, and artificial islands were added for upstream ice stability. Coast Guard icebreakers were also a necessary part of winter navigation in this area.